Alfabetização e ortografia - Cagliari, Luiz Carlos (Educar em Revista, 2002)
A ortografia era uma das metas mais importantes na metodologia das cartilhas. Com o advento de novas metodologias, as cartilhas deixaram de ser usadas. Nas novas abordagens, a ortografia passou a ocupar um lugar secundário na alfabetização ou mesmo ficou excluída. Essa atitude com relação à ortografia representa um retrocesso educacional. Sem o método das cartilhas e sem informações técnicas sobre a ortografia, muitos professores se viram na situação de não saber o que fazer. O presente trabalho apresenta algumas das noções básicas que definem e caracterizam a ortografia e, além disso, sugere procedimentos metodológicos. Literacy and orthography Abstract Spelling used to be one of the primary goals in the Brazilian Cartilha teaching methodology. With new approaches to literacy process in the past twenty years, the old Cartilha method is no more in use. On the other hand, teaching of spelling has been withdrawn from literacy activities. This procedure is misleading and it represents a serious problem for teachers and students. Without the old rigid methodology to literacy teachers, and with a lack of information to understand orthography nature and uses of orthography, teaching became chaotic, in this respect. This paper aims to report basic notions that characterise orthography as a special writing phenomenon, and at the same time to show methodological suggestions on how to deal with spelling in this new educational context.